FINANCIAL ACCESS TO HIGHER EDUCATION: RUSSIA VS USA - E. V. Bogomolov (Финансы: теория и практика, 2017)
In the innovation economy the higher vocational education is getting inseparable from the concept of «educated person», i.e. becomes universal in nature. The ever-increasing demand for higher education among the population leads to the problem of accessibility of quality higher education.The paper focuses on the financial aspect of the access to higher education.The concept of the financial affordability is clarified; the affordability index calculated on the median salary basis is proposed. A method for calculatiing the higher education affordability index for ten leading Russian and ten leading American universities is described. Based on the data obtained it is concluded that the access to quality higher education is higher in the Russian Federation than in the USA. However, the education at the most cost expensive US University is financially more affordable than the similar education for Russian students.Measures to improve the financial affordability of higher education based on educational loans are proposed.